A case which hepatic lipoma and renal angiomyolipoma seen in the same patient - Kargici, H.; Cifter, C.; Yalcin, O. (My University, 1996)
We describe a lipoma of the liver and a renal angiomyolipoma which are very rare benign tumors seen together in the same patient. This will be the second case described in the literature. Usually preferred treatment is conservative for both tumors. However, for the risk of spontaneous hemorrhage in renal angiomyolipomas surgical treatment may be necessary.
KARACIGER LIPOMU VE BOBREK ANJIOMYOLIPOMU'NUN BIRLIKTE BULUNDUGU BIR OLGU
Keywords: Lipoma of the liver; Renal angiomyolipoma; Surgical treatment